Main provisions and benefits of the Geneva Act of the Lisbon Agreement (2015). (World Intellectual Property Organization (WIPO), 2021)
The Geneva Act of the Lisbon Agreement was adopted by the Diplomatic Conference for the Adoption of a New Act of the Lisbon Agreement for the Protection of Appellations of Origin and their International Registration, which took place in Geneva from May 11 to 21 , 2015. The Act establishes an international system of registration and protection for both appellations of origin and geographical indications.
Keywords: Intellectual property (International law); Marks of origin.